Wepwawet and Anubis, Two Egyptian Canid Gods Mutually Complementing Their Funerary Roles - Bontempo, Sofía (Eikón / Imago, 2015)
The belief in life after death has been present in Egyptian civilization since its very beginnings. The early burial sites were frequently an easy prey for predators that roamed the desert, especially jackals. The sight of these animals next to bodies mummified under natural conditions fostered the belief that these animal figures were guides of souls into the Underworld. Among the Egyptian canid gods, two stand out in their funeral roles: Anubis and Wepwawet. Within the Egyptian funerary imagery, both gods perform specific roles. Each of their functions alternate and complement each other’s, perhaps continuing the pattern of duality present in Egyptian society itself and reflected in its art. The definitive role of these two gods would be watching over and protecting the deceased on their way to the Underworld. In this sense, they can be considered as being two complementary facets that provide protection during the passage into the world of the dead.